Dari Limbah ke Lahan Subur: Pemanfaatan Kotoran Kambing dan Tanaman Liar untuk Pertanian Berkelanjutan - Ilham, Andi; Ramdani, Raehan; Sabani, Sulita; Lestari, Dia; Safitri, Gitta; Iqrom, Muhammad; Guteres, Fikri; Rafsanjani, Reza; Latifa, Lala; Nisa, Baiq (Universitas Mataram, 2025)
The background of this activity is the need to address the issue of goat manure and wild plant waste, which pose environmental problems in the village. The objective of this activity is to provide an environmentally friendly solution in the form of solid and liquid organic fertilizers to support sustainable agriculture. The methods of this activity include socialization, training, and distribution of plant seedlings using organic fertilizer-based planting media. The results show that solid organic fertilizer provides a balanced supply of macro and micronutrients, while liquid fertilizer enhances plant nutrient absorption efficiency. This program has economic, social, and environmental impacts by improving soil fertility, reducing dependency on chemical fertilizers, and creating business opportunities. The conclusion indicates that this initiative offers an innovative and sustainable solution for rural communities.